# Multiply:(i) $\frac{7}{11}$ by $\frac{5}{4}$(ii) $\frac{5}{7}$ by $\frac{-3}{4}$(iii) $\frac{-2}{9}$ by $\frac{5}{11}$(iv) $\frac{-3}{17}$ by $\frac{-5}{-4}$(v) $\frac{9}{-7}$ by $\frac{36}{-11}$(vi) $\frac{-11}{13}$ by $\frac{-21}{7}$(vii)$-\frac{3}{5}$ by $-\frac{4}{7}$(viii) $-\frac{15}{11}$ by 7

To do:

We have to multiply the following rational numbers

Solution:

(i) Multiplying $\frac{7}{11}$ by $\frac{5}{4}$

$\frac{7}{11}\times\frac{5}{4}=\frac{7\times5}{11\times4}$

$=\frac{35}{44}$

(ii) Multiplying $\frac{5}{7}$ by $\frac{-3}{4}$

$\frac{5}{7}\times\frac{-3}{4}=\frac{5\times(-3)}{7\times4}$

$=\frac{-15}{28}$

(iii) Multiplying $\frac{-2}{9}$ by $\frac{5}{11}$

$\frac{-2}{9}\times\frac{5}{11}=\frac{(-2)\times(5)}{9\times11}$

$=\frac{-10}{99}$

(iv) Multiplying $\frac{-3}{17}$ by $\frac{-5}{-4}$

$\frac{-3}{17}\times\frac{-5}{-4}=\frac{(-3)\times(-5)}{17\times(-4)}$

$=\frac{15}{-68}$

$=\frac{-15}{68}$

(v) Multiplying $\frac{9}{-7}$ by $\frac{36}{-11}$

$\frac{9}{-7}\times\frac{36}{-11}=\frac{(9)\times(36)}{(-7)\times(-11)}$

$=\frac{324}{77}$

(vi) Multiplying $\frac{-11}{13}$ by $\frac{-21}{7}$

$\frac{-11}{13}\times\frac{-21}{7}=\frac{(-11)\times(-21)}{(13)\times(7)}$

$=\frac{11\times3}{13\times1}$

$=\frac{33}{13}$

(vii) Multiplying $-\frac{3}{5}$ by $-\frac{4}{7}$

$-\frac{3}{5}\times-\frac{4}{7}=\frac{(-)\times(-)\times3\times4}{(5)\times(7)}$

$=\frac{12}{35}$

(viii) Multiplying $-\frac{15}{11}$ by 7

$-\frac{15}{11}\times\frac{7}{1}=-\frac{15\times7}{11}$

$=-\frac{105}{11}$

Tutorialspoint

Simply Easy Learning

Updated on: 10-Oct-2022

21 Views

##### Kickstart Your Career

Get certified by completing the course